A cross‐sectional analysis of factors associated with stress, burnout and turnover intention among healthcare workers during the COVID‐19 pandemic in the United States. (17th January 2022) - Mercado, Micaela; Wachter, Karin; Schuster, Roseanne C.; Mathis, Cherra M.; Johnson, Emma; Davis, Olga Idriss; Johnson‐Agbakwu, Crista E.
Abstract: In 2020, healthcare workers faced the COVID‐19 pandemic amidst other salient sociopolitical stressors. This study, therefore, set out to examine associations between personal, work‐related and contextual factors and three outcomes – stress, burnout and turnover intention – at a critical juncture in the pandemic. In December 2020, we recruited a broad array of healthcare workers ( n  = 985) in a public safety net healthcare system serving socially and economically marginalised communities in the Southwest region of the United States using a cross‐sectional online survey. The results indicated that more health problems were associated with higher stress and burnout symptoms. While seeking emotional support and using drugs or alcohol to cope were associated with higher stress, a positive social outlook was associated with lower stress. Lower quality of work‐life was associated with higher burnout symptoms and turnover intention. Negative effects of the pandemic on wellbeing and higher number of COVID‐19‐related concerns were associated with higher stress and burnout symptoms. Contrary to the original hypotheses, self‐care was not associated with any of the three outcomes, and effects of the political climate and issues of racism on wellbeing were not associated with stress, burnout or turnover intention. However, identifying as a Person of Colour was associated with higher stress, as well as lower burnout. The findings on worker health, social outlook, quality of work‐life and race/ethnicity, in particular, suggest a critical need for healthcare systems to address the wellbeing of workers through equitable organisational policy and practice.